Legal Protection of Retail Investors' Personal Data in The Digital Stock Trading Ecosystem: A Case Study of Stockbit Indonesia - Naufal Sheva Alfauzi; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2026)
The digital transformation of the capital market through securities companies like Stockbit has broadened retail investor access, but it also poses risks to personal data protection. This research uses a normative legal method with a statutory approach, referring to Law Number 27 of 2022 concerning Personal Data Protection and supported by secondary and tertiary legal materials. The results of this study indicate that although a legal framework governing data protection obligations exists, its implementation is not optimal, as reflected in the case of system disruptions and administrative sanctions against PT Stockbit Sekuritas Digital. The effectiveness of investor personal data protection depends heavily on the consistent implementation of legal obligations, strengthened oversight, and increased accountability of digital investment platform providers.